Franco Fortini e la psicoanalisi come metodo. Per un’angoscia lirica oltre il sintomo letterario - Binetti, Roberto (L’ospite ingrato, 2023)
The article explores the controversial and complex relationship that Fortini maintains with psychoanalysis throughout his literary career. Since the early forties, this relationship is primarily manifested through his production of critical essays, reviews, and, in a more subtle manner, within the fabric of his lyric texts. Fortini integrates psychoanalysis into his critical approach through a complex stratification of methods and references (Freud, Jung, Lacan, Fachinelli, Orlando) that are carefully tailored to the specific work or subject of study to which the text is dedicated. The central focus of his interest lies in identifying a tool that can connect the “other” of the text, considered a laboratory of political writing, to the other recipients of the same text through the expression of a sense of “lyric anxiety.”